Hazard Risk Management for Occupational Safety and Health on Phinisi Shipbuilding - Ibrahim, Hasbi; Aris, Kiky Afriani Andi (Al-Sihah: The Public Health Science Journal, 2022)
The implementation of the making process of a Phinisi ship has a potential hazard impact on occupational safety and health, including the tools, materials, and work processes respectively. One of the accident risk management methods used is called the Hazard and Operability method, which reviews the process of making a Phinisi ship in order to identify some hazards and analyze the risk of work accidents. The purpose of this study was to use hazard and operability (HAZOP) to assess the level of occupational health and safety risk for Phinisi ship workers. This research was quantitative with a descriptive approach because it described the risk of work accidents in making Phinisi Ships. The population in this study were all Phinsi ship workers, whilst the sampling technique was total sampling. The results showed that the hazards identified in the Phinisi shipbuilding process were physical, chemical, physiological, and mechanical hazards. The most dominant hazard identified in each work step process was a physical hazard. At the stage of making ivory or ship hulls, there was a very high level of possible risk. In addition, at the work step of installing ship sails, the severity of the risk was very serious. This study led to a systematic evaluation of the possible risks and a suggestion for how industrial managers can reduce the risks that come up when building ships.